The early Industrial Revolution in the Leen valley, Nottinghamshire - Walker, Stephen J. (2017)
At Papplewick, Nottinghamshire, there is physical evidence of 18th century industry. This study focuses on George Robinson and Sons, who were cotton-spinners between 1778 and 1830. The firm’s records have not survived, so detail of their operation has been re-constructed using alternative sources. The thesis investigates some accepted ideas about the concept of industrialisation, and attempts to address the question of when, where and what constituted the Industrial Revolution in this particular locality. The study adopts a transdisciplinary approach, viewing physical evidence from the landscape alongside documentary sources. Evidence from archaeological exploration is presented. The historic landscape is viewed in the context of biographical and socio-economic data relating to people and events. These water-powered mills were the first in the world to apply steam to cotton-spinning. The study considers the evolution of the water-system, and the introduction of steam to this pioneer site. It also examines transport networks, delivery of raw materials and capital expenditure. Personnel associated with the mills are identified, charting their employment and migration. Cartographic sources of different ages are used to provide a spatial framework for the description. The principles of reverse engineering are applied - attempting to understand, on one hand, the function of the mills and water-system, and on the other to de-construct the factors which influenced this innovative undertaking. It is generally accepted that three key attributes of the Industrial Revolution were adoption of new technology, introduction of centralised production, and socio-economic changes, accompanied by urbanisation. The Robinson mills could be perceived as the beginning of the Industrial Revolution in the Leen valley. However, when the company was wound up (in 1830) industrial activity in the valley reverted to manufacture of hosiery and bobbin-net lace, both of which were, at that time, cottage industries.